Pastoral care matters in primary and middle schools - David, Kenneth; Charlton, Tony (Routledge, 1996)
This wide ranging book offers a fresh survey of the pastoral needs of primary age pupils, and pupils in early adolescence for both trainee and practising teachers. This book is divided into four main sections:* Principles considers the future needs of children, learning processes, the planning and implementation of a pastoral programme, and the co-ordination of personal and social education* Aspects of Pastoral Care develops six specific pastoral approaches: welfare and liaison, health and medical services, life crises and counselling, managing behavio.